1981
DOI: 10.1159/000299597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation in Pregnancy

Abstract: Serum calcium, inorganic phosphate and heat-labile alkaline phosphatase (HLAP) have been estimated in maternal and cord sera of 120 pregnant women at labour. 75 women who did not take any vitamin D supplements during pregnancy showed statistically significant hypocalcaemia, hypophosphataemia and elevation of HLAP. Hypocalcaemia and hypophosphataemia were present in cord blood, too. 25 women who had received 1,200 U vitamin D/day throughout the 3rd trimester, showed significantly lower HLAP levels and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
101
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 18 publications
5
101
0
4
Order By: Relevance
“…This study also found an association between the vitamin D receptor genotype and SGA risk, and both maternal vitamin D status and vitamin D receptor genotype were independent risk factors for SGA. Morley et al (22) also found an association of the vitamin D receptor (12)(13)(14)(15)(16)(17) .…”
Section: Effects Of Maternal Vitamin D Deficiency On Fetal Growth Andmentioning
confidence: 94%
See 3 more Smart Citations
“…This study also found an association between the vitamin D receptor genotype and SGA risk, and both maternal vitamin D status and vitamin D receptor genotype were independent risk factors for SGA. Morley et al (22) also found an association of the vitamin D receptor (12)(13)(14)(15)(16)(17) .…”
Section: Effects Of Maternal Vitamin D Deficiency On Fetal Growth Andmentioning
confidence: 94%
“…5 % among breast-fed and formula-fed infants of mothers who did not receive vitamin D supplements. These observational studies were followed by several randomised trials of vitamin D supplementation during pregnancy (12)(13)(14)(15)(16)(17)(18) .…”
Section: Effects Of Maternal Vitamin D Deficiency On the Neonatal Camentioning
confidence: 99%
See 2 more Smart Citations
“…Improved liver enzyme levels in cord blood (CB) of the infants whose mothers received one dose of 1 500 μg vitamin D3 in the second trimester or 2 doses of 3 000 μg vitamin D3 each in the second and third trimesters were seen compared with the controls [18]. In another study by Marya et al [33] supplementation with 2 large doses of 600 000 IU each in the 7 th and 8 th months has led to a significant improvement in serum liver enzyme in [17,34]. In addition, maternal hyperglycemia and the subsequent induction of fetal hyperinsulinemia as well as reduced oxygenation are hypothesized to result in increased fetal oxygen uptake, fetal erythropoiesis, and subsequent hyperbilirubinemia [35].…”
mentioning
confidence: 97%